AKUNTABILITAS PEMERINTAH TERHADAP PELAYANAN PUBLIK DI DESA BOLA BULU KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Ayu Angreani; Herman Dema (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract This study aims to determine the government's accountability for public services in Bola Bulu Village, Pitu Riase District, Sidenreng Rappang Regency. The population of this study was 35 people and a sample of 35 people. The sampling technique used is a saturated sampling (census). This type of research is a quantitative descriptive. Data collection techniques are observation, interviews, library research, and questionnaires. Data analysis techniques use statistics. The results showed that government accountability was 60% less good, covering 57% law, 66% honesty, 55% managerial, 61% program, 56% policy, and 64% financial. While public services 65% are good, covering simple 58%, clear 58%, security 68%, open 73%, efficient 66%, economical 67%, and justice 63%. This shows that the government's accountability for public services in Bola Bulu Village, Pitu Riase District is 62% of the 100% expected result, which is classified as